Rheology of PA-6/EPM/EPM-g- MA Blends Along a Twin-Screw Extruder - Covas, J. A. (2000)
The changes in the rheological behavior, morphology, and chemical conversion of PA-6/EPM/EPM-g-MA blends (80/20/0 to 80/0/20; w/w/w) along a compounding co-rotating twin-screw extruder were monitored. The linear viscoelastic behavior of nonreactive and reactive blends could be interpreted in terms of morphology and/or chemical conversion. However, a quantitative prediction of the rheological response using Lee and Park’s theory, which relates the rheological behavior with morphological changes of polymer blends, taking into account coalescence and breakup phenomena, was not possible because of the observed degradation of PA-6 along the screw. Matrix degradation also explains the low viscosity levels of the blends when compared with those of the original materials.